Perceived health inequalities: are the UK and US public aware of occupation-related health inequality, and do they wish to see it reduced? - Emma K. Bridger; Angela Tufte-Hewett; David A. Comerford (BMC, 2023)
Abstract Background One underexamined factor in the study of lay views of socioeconomic health inequalities is occupation-related health. Examining health by occupational social class has a long history in the UK but has been comparatively overlooked in US public health literatures, where the relationship between health and work has attended more to hazard exposure. Methods Representative samples of the UK and US indicated the perceived and ideal lifespan of people working in "higher managerial/professional" and "routine" occupations. We examine perceptions of inequality and desires for equality across occupation groups as a function of country and key socio-demographic variables. Results 67.8% of UK and 53.7% of US participants identified that professionals live longer than routine workers. Multivariate models indicated that US participants were markedly less likely to be aware of occupation-related inequalities after controlling for age, gender, and education. Awareness was negatively related to age (in the US) and recent voting behaviours (both samples). Desiring equal life expectancy was less likely in the US sample, and less likely across both samples among older participants and those with lower levels of education. Conclusion Employing a novel approach to measuring perceived and ideal life expectancy inequality, this is the first study to examine perceptions of lifespan inequality by occupational groups. It reports widespread understanding of the occupation-related gradient in lifespan and a desire that these inequalities be eliminated in the UK, but considerably less awareness and desire for equality in the US. Greater tolerance for social status inequalities in the US than other similar countries appear to also extend to differences in life expectancy.